Period-multiplying cycles at the transition between stick-slip and stable sliding and implications for the Parkfield period-doubling tremors - Mei, Cheng (2022)
The recurrence patterns of the Parkfield tremors with period-multiplying slow and fast ruptures provide new insights on the physics of earthquake cycles. However, the mechanisms behind the peculiar recurrence pattern and the coupling between slow-slip events and seismic radiations are still unclear. Here, we conduct direct-shear experiments on polycarbonate and granite fractures under varying stress conditions to investigate the variations of rupture properties near the stability transition. Laboratory slow and fast ruptures sequences produce slip-predictable period-multiplying cycles with correlative acoustic energy release, stress drop, event duration, and recurrence intervals. However, gouge accumulation by damage of the granite fracture provokes changes in stiffness and stress drops ratios over multiple cycles, affecting the recurrence intervals and energy release of consecutive slip events. These findings confirm the link between low-frequency earthquakes and underlying slow-slip events, with period-multiplying cycles naturally occurring near the stability transition.